Evaluasi Usability Aplikasi PAK RT Berbasis WebGIS Menggunakan Model Nielsen - S. Candra Hastuti H.; Gunadi Gunadi; Ahmad Redha Arissaputra (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Prajuritkulon District, located in the City of Mojokerto, utilizes an innovative application called PAK RT (Neighborhood Supervision) to collect, display, and map data related to public order and security conditions within the district. The system was initially developed in 2022; however, it did not function effectively and was ultimately not utilized. In 2024, the system underwent a redesign. To evaluate the usability of the redesigned system, this study employed usability testing based on the Nielsen model, which includes Learnability, Efficiency, Memorability, Errors, and Satisfaction. The evaluation followed a series of procedural steps, including scenario-based testing, administration of the Nielsen Attributes of Usability (NAU) questionnaire, and interviews with administrative village operators. The results indicate positive usability outcomes, with scores of 74,93% for Learnability, 66,65% for Efficiency, 83,33% for Memorability, 69,44% for Errors, and 85,89% for Satisfaction. These findings suggest that neighborhood operators are delighted with the features and benefits of the web-based PAK RT application. Consequently, the redesign is considered successful in meeting reporting needs and providing added value to users.